Changes in energy metabolism in pheochromocytoma - Petrák, O; Haluzíková, D; Kaválková, P; Štrauch, B; Rosa, J; Holaj, R; Brabcová Vránková, A; Michalsky, D; Haluzík, M; Zelinka, T; Widimsky, J (The Journal of clinical endocrinology and metabolism, 2013)
CONTEXT: Catecholamine overproduction in pheochromocytoma affects basal metabolism, resulting in weight loss despite normal food intake. OBJECTIVE: The objective of the study was to evaluate changes in energy metabolism expressed as resting energy expenditure (REE) in patients with pheochromocytoma before and after adrenalectomy and the possible relationship with circulating inflammatory markers. DESIGN: We measured REE in 17 patients (8 women) with pheochromocytoma by indirect calorimetry (Vmax-Encore 29N system) before and 1 year after adrenalectomy. Body fat percentage was measured with a Bodystat device. Inflammatory markers (leukocytes count and C-reactive protein) and cytokines (TNF-α, IL-6, and IL-8) were analyzed with a Luminex 200. RESULTS: REE measured in the pheochromocytoma group was 10.4% higher than the predicted value (1731 ± 314 vs 1581 ± 271 kcal/d; P = .004). Adrenalectomy significantly increased body mass index (P =0.004) and the percentage of body fat (P = .01), with a proportional increase in fat distribution (waist circumference, P = .045; hip circumference, P = .001). REE significantly decreased after adrenalectomy (1731 ± 314 vs 1539 ± 215 kcal/d; P = .002), even after adjustments in body surface and body weight (P < .001). After adrenalectomy, we found a significant decrease in leukocyte counts (P = .014) and in the levels of TNF-α (P < .001), IL-6 (P = .048), and IL-8 (P = .007) but not C-reactive protein (P = .09). No significant correlations among calorimetry parameters, hormones, and proinflammatory markers were detected. CONCLUSIONS: Chronic catecholamine overproduction in pheochromocytoma may lead to a proinflammatory and hypermetabolic state characterized by increased REE. Adrenalectomy leads to the normalization of energy metabolism followed by an increase in body mass index and body fat content and decreases in inflammatory markers and cytokines.
Keywords: adrenalektomie; tuková tkáň; velikost orgánu; Humans; lidé středního věku; Adrenal Gland Neoplasms; složení těla; Pheochromocytoma; Adrenalectomy; Female; Aged; dospělí; katecholaminy; senioři; lidé; Basal Metabolism; Adult; Energy Metabolism; ženské pohlaví; energetický metabolismus; Male; Middle Aged; Body Composition; nádory nadledvin; Catecholamines; Body Weight; Organ Size; tělesná hmotnost; mužské pohlaví; bazální metabolismus; Adipose Tissue; feochromocytom